Study of Method for Measuring Capacity of Shallow Foundation in Different Models that Suitable for the Construction Site of Luang Prabang Capital City Area Case Study: Ban Donmai Campus, Souphanouvong University - Sitthivong, Phouthamala; Bounxayyavong, Somsanouk; Houngpaerth , Sisouphan; Simmavong, Khongseng; Thavongsy, Boulaphant (Souphanouvong University Journal Multidisciplinary Research and Development, 2023)
This research study to demonstrate the various methods used to calculation value of bearing capacity for shallow foundation, to be a multiple choice method for assessing the uptake rate of value of bearing capacity for shallow foundation, as well as to apply the soil formulas and theories were collected borehole soil data and comparation the value of bearing capacity of soil to be safety using each methods of soil property. The geological, engineering characteristics and mechanical characteristics of the soil in the study area are very important. The purpose was to study the shear strength and bearing capacity for shallow foundation and the suitability of each method suitable for use in the Souphanuvong University area. The results of calculating the bearing capacity of shallow foundations (Bearing capacity) by equipment and theoretical methods 1. Terzaghi, 2. Meyerhof, 3. Vesic, 4. Hansen and 5. Ohsaki. And small fundamental changes. For the method parts of 1. Meyerhof, 2. Hansen, 3. Vesic are suitable for bases receiving zero force (not at the center of the foundations) and inclined force.